PERBEDAAN PENGETAHUAN SEBELUM DAN SESUDAH DIBERI PENYULUHAN TENTANG DYSMENORHEA (NYERI HAID) PADA REMAJA PUTRI KELAS VII SMP MA’ARIF 1 PONOROGO - Rindang Fitria Ulfa (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Dysmenorhea (painful menstruation) conditions often experienced by teenagersduring menstruation. Preliminary studies conducted on 8 students interviews obtained 3to explain the meaning dysmenorhea (painful menstruation), while 5 students are notable to explain the meaning dysmenorhea (painful menstruation). This shows kuragnyastudent knowledge. The study aims to determine differences in knowledge of adolescentgirls before and after counseling.Based on the objectives of the research design used pre Experimental designresearch methods one group pretest posttest. The entire study population grader SMPMa'Arif 1 sempel ponorogo 41 respondents and 41 female students (total sampling).2variabel independent variables used are differences in knowledge before and after thegiven counseling about dysmenorhea (painful menstruation). Use traditional methods ofdata collection questionnaire is then processed with Editing, Coding, Scoring,Tabulating and analyzed.The results showed that the respondents' knowledge before counseling knowledgeeither 15 (36.6%), respondents were knowledge enough 22 (53.6%), and 4 (9.8%) lessknowledge respondents, while the counseling is done after both knowledge respondents36 (87.8%), respondents were knowledge enough 5 (12.2%), and no less knowledgerespondents (0%). From the calculation of the statistical test T-test with a significancelevel of 0.05 that ρ <ɑ 0.05, Ha is accepted that there is an increase in knowledge amongyoung women received counseling before and after receiving counseling on dysmenorhea(painful menstruation).Young women are expected to further expand the knowledge and references ondysmenorhea (painful menstruation). The school is expected to give a lesson orcounseling about dysmenorhea (painful menstruation) in adolescent girls as an extra.